2008
DOI: 10.1016/j.febslet.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

UCP3 overexpression neutralizes oxidative stress rather than nitrosative stress in mouse myotubes

Abstract: a b s t r a c tThe deleterious effects of oxidants on proteins may be modified by overexpression of uncoupling protein 3 (UCP3) in skeletal muscle cells exposed to hyperoxia or H 2 O 2 . UCP3 overexpression significantly attenuated the increase in protein carbonylation in response to hyperoxia and H 2 O 2 exposures. However, antioxidant enzyme content and activity (superoxide dismutases, peroxiredoxins, glutathione peroxidase-I, and catalase) were reduced or not modified in UCP3-overexpressing myotubes exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…It has been reported that excessive expression of the UCP3 gene in human skeletal muscle can promote glucose intake and lead to enhance glucose and lipid oxidation, similarly to our results. 23,24) Our study found that the JAK2/STAT3 signal pathway might regulate the body's energy metabolism by enhancing the expression of genes that are implicated in energy metabolism.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that excessive expression of the UCP3 gene in human skeletal muscle can promote glucose intake and lead to enhance glucose and lipid oxidation, similarly to our results. 23,24) Our study found that the JAK2/STAT3 signal pathway might regulate the body's energy metabolism by enhancing the expression of genes that are implicated in energy metabolism.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, since mitochondrial uncoupling has been reported to reduce the production of reactive oxygen species [28,29], we monitored superoxide production in OCI-AML3 cells by flow cytometry. As evidenced in Fig.…”
Section: Platelet Contents Promote Mitochondrial Uncoupling and Antagmentioning
confidence: 99%
“…In fact, UCPs reduce the damaging effects of ROS during cardiac ischemia/reperfusion injury (Barreiro et al, 2009). UCP1 isoform is involved in thermogenesis and expressed specifically in brown adipose tissue mitochondria, in which it confers a regulated proton leak across the inner membrane, whereas the physiologic functions of the other isoforms remain unclear.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%